Penyitaan Kekayaan sebagai Pelunasan Pidana Denda: Dapatkah Mencapai Tujuan Pemidanaan? - Ardiansah, Mohammad Didi; Sholihah, Afnan Zahidatush (Kertha Patrika, 2024)
The aim of this research is to examine the extent of limitations on the seizure of a convict's assets or income to settle criminal fines, as well as its relation to the objectives of punishment under the Law Number 1 of 2023 concerning Criminal Code (National Criminal Code). This research employs a normative juridical method with a statutory approach. The research conclude that the provisions for seizing a convict's assets or income to settle unpaid fines can support the achievement of the objectives of punishment under the National Criminal Code. However, to attain this goal, there must be provisions defining the limits on the convict's assets or income that may be seized. The construction of such limits can adopt the provisions on seizure as regulated in the Indonesian Civil Procedure Code (HIR) and the Bankruptcy/PKPU Law. TRANSLATE with x English Arabic Hebrew Polish Bulgarian Hindi Portuguese Catalan Hmong Daw Romanian Chinese Simplified Hungarian Russian Chinese Traditional Indonesian Slovak Czech Italian Slovenian Danish Japanese Spanish Dutch Klingon Swedish English Korean Thai Estonian Latvian Turkish Finnish Lithuanian Ukrainian French Malay Urdu German Maltese Vietnamese Greek Norwegian Welsh Haitian Creole Persian   //   TRANSLATE with COPY THE URL BELOW Back EMBED THE SNIPPET BELOW IN YOUR SITE setTimeout(function(){var s=document.createElement('script');s.type='text/javascript';s.charset='UTF-8';s.src=((location && location.href && location.href.indexOf('https') == 0)?'https://ssl.microsofttranslator.com':'http://www.microsofttranslator.com')+'/ajax/v3/WidgetV3.ashx?siteData=ueOIGRSKkd965FeEGM5JtQ**&ctf=true&ui=true&settings=manual&from=en';var p=document.getElementsByTagName('head')[0]||document.documentElement;p.insertBefore(s,p.firstChild); },0); "> Enable collaborative features and customize widget: Bing Webmaster Portal Back // ORIGINAL: "; langMenu.appendChild(origLangDiv); LanguageMenu.Init('LanguageMenu', LanguageMenu_keys, LanguageMenu_values, LanguageMenu_callback, LanguageMenu_popupid); window["LanguageMenu"] = LanguageMenu; clearInterval(intervalId); } }, 1); // ]]>